Professional learning and TVET: challenges and perspectives for teachers and instructors - Harteis, Christian (International handbook of education for the changing World of Work)

Lernen von Lehrenden im Arbeitsprozess - Mulder, Regina H; Harteis, Christian; Gruber, Hans (Lehrprofessionalität - Bedingungen, Genese, Wirkungen und Messung)

Mikroanalytische Begleitung der Steuerpolitik am Beispiel der Erbschaftsteuerreform - Maiterth, Ralf; Houben, Henriette; Broekelschen, Wiebke; Müller, Jens; Sureth-Sloane, Caren (Statistik und Wissenschaft)
Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation | Deutschland | Germany
Keywords: Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation

Wirtschaft und Betrieb - Heid, Helmut; Harteis, Christian (Handbuch Bildungsforschung)

Hierarchisches Clustering mit minimalen Cluster-Durchmessern - Schröer, Carsten

Teacher Collaboration Concerning ICT-Use and its Essential Conditions - Schulz-Zander, Renate; Eickelmann, Birgit (Proceedings – 9th WCCE. IFIP World Conference on Computers in Education)

E-teaching plus. Die webbasierte Lernumgebung für situiertes Lernen mit Unterrichtsvideos - Schulz-Zander, Renate; Eickelmann, Birgit

National Policies and Practices on ICT in Education: Germany - Schulz-Zander, Renate; Eickelmann, Birgit (Cross-national Information and Communication Technology. Policies and Practices in Education)

Analyse und Evaluation eines identitätsbasierten Signcryption-Verfahrens - Liske, Gennadij

Die Schwierigkeit des k-Median Clusterings für Bregman-Divergenzen - Scholz, Christoph

Algorithms for the Bregman k-Median Problem - Ackermann, Marcel Rudolf

Reinforcement Learning for Blackjack - Kakvi, Saqib (Lecture Notes in Computer Science)

Coresets and Approximate Clustering for Bregman Divergences - Ackermann, Marcel R.; Blömer, Johannes (Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms)

Sampling methods for shortest vectors, closest vectors and successive minima - Blömer, Johannes; Naewe, Stefanie (Theoretical Computer Science)
Keywords: Geometry of numbers; Lattices; Shortest vectors

Three-Valued Spotlight Abstractions - Schrieb, Jonas; Wehrheim, Heike; Wonisch, Daniel (FM 2009: Formal Methods)

Linkages between Financial Deepening, Trade Openness and Economic Development: Causality Evidence from Sub-Saharan Africa - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (World Development)

The Optimal Distance to Port for Exporting Firms - Gries, Thomas; Naudé, Wim (Journal of Regional Science)

Explaining Regional Export Performance in a Developing Country: The Role of Geography and Relative Factor Endowments - Gries, Thomas; Naudé, Wim (Regional Studies)

Entrepreneurship and regional economic growth: towards a general theory of start-ups - Gries, Thomas; Naudé, Wim (Innovation: The European Journal of Social Science Research)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (Advances in Cryptology - ASIACRYPT 2009, 15th International Conference on the Theory and Application of Cryptology and Information Security, Tokyo, Japan, December 6-10, 2009. Proceedings)

Modifications in Dietary Fat Quality Are Associated with Changes in Serum Lipids of Older Adults Independently of Lipid Medication - Buyken, Anette; Flood, Victoria; Rochtchina, Elena; Nestel, Paul; Brand-Miller, Jennie; Mitchell, Paul (The Journal of Nutrition)

Immigrational Background Affects the Effectiveness of a School-based Overweight Prevention Program Promoting Water Consumption - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Toschke, André M.; Reinehr, Thomas; Kersting, Mathilde (Obesity)

Relative validity of a self-completion 24 h recall questionnaire to assess beverage consumption among schoolchildren aged 7 to 9 years - Muckelbauer, Rebecca; Libuda, Lars; Kersting, Mathilde (Public Health Nutrition)
Abstract Objective Drinking habits in children are associated with diet quality, but validated assessment tools for large-scale studies in young children are lacking. Therefore, we validated a self-completion 24 h recall questionnaire (RQ) focusing on beverage consumption with a 24 h weighed record (WR). Design Thirty-five voluntary participants from the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) Study cohort aged 7–9 years completed the RQ. The illustrated RQ required ticking the number of glasses of seven beverage categories consumed in five time intervals in the previous 24 h. As a reference, parents completed weighed records of their child’s diet. Agreement between the RQ and WR was tested by classification into consumers and non-consumers (kappa coefficients, κ ), by the children’s ability to estimate the exact beverage and total volume consumed (Wilcoxon signed-rank test, Spearman rank correlation), and by ranking children according to reported beverage volumes. Results The RQ and WR showed a good level of agreement for classifying participants into consumers and non-consumers of the single beverage categories ( κ values between 0·78 and 0·94). Correlation coefficients for the volume of the single categories ranged between 0·81 and 0·91. The total beverage volume was overestimated in the RQ, on average, by 114 ml ( P = 0·015). Agreement in ranking into tertiles by beverage volume was moderate to good for juice/soft drinks ( κ = 0·44), milk ( κ = 0·57) and water ( κ = 0·70), but fair for the total beverage volume ( κ = 0·23). Conclusions Our self-completion 24 h RQ could estimate the consumption of several beverage categories among young children at the group level, but quantification of total beverage volume was flawed.

Relation of Dietary Glycemic Index, Glycemic Load, and Fiber and Whole-Grain Intakes During Puberty to the Concurrent Development of Percent Body Fat and Body Mass Index - Cheng, G.; Karaolis-Danckert, N.; Libuda, Lars; Bolzenius, K.; Remer, T.; Buyken, Anette E. (American Journal of Epidemiology)

Long-term process evaluation of a school-based programme for overweight prevention - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Kersting, M. (Child: Care, Health and Development)

A Simple Dietary Intervention in the School Setting Decreased Incidence of Overweight in Children - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Reinehr, Thomas; Kersting, Mathilde (Obesity Facts)

Promotion and Provision of Drinking Water in Schools for Overweight Prevention: Randomized, Controlled Cluster Trial - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Toschke, A. M.; Reinehr, T.; Kersting, M. (PEDIATRICS)

Erfolgreich Computer und Internet in Grundschulen integrieren – eine empirische Analyse aus Sicht der Schulentwicklungsforschung - Eickelmann, Birgit; Schulz-Zander, Renate; Gerick, Julia (Europäisierung der Bildung - Konsequenzen und Herausforderungen für die Grundschulpädagogik)

The Dagstuhl Core - Dumitrescu, Theodor; Kepper, Johannes; Kornstädt, Andreas; Röwenstrunk, Daniel; Roland, Perry; Sapp, Craig; Selfridge-Field, Eleanor; Wiering, Frans; Wiggins, Geraint A.

Soft drinks and body weight development in childhood: is there a relationship? - Libuda, Lars; Kersting, Mathilde (Current Opinion in Clinical Nutrition and Metabolic Care)

Getränkeverzehr und Übergewicht bei Kindern - Libuda, Lars; Muckelbauer, R.; Kersting, M. (Journal für Ernährungsmedizin)

Einfluss des Konsums von Erfrischungsgetränken auf den Ernährungs- und Gesundheits¬status von Kindern - Libuda, Lars (Ernährungsumschau)

DONALD News: Zusammenhang zwischen dem Verzehr von Erfrischungsgetränken und dem Knochenstatus von Kindern und Jugendlichen. - Libuda, Lars; Remer, Thomas; Kersting, M. (Ernährungsumschau)

Associations of fat and cholesterol intake with serum lipid levels and cardiovascular disease: The EURODIAB IDDM Complications Study* - Toeller, M.; Buyken, Anette; Heitkamp, G.; Scherbaum, W.A.; Krans, H.M.J; Fuller, J.H. (Experimental and Clinical Endocrinology & Diabetes)

A new FFQ designed to measure the intake of fatty acids and antioxidants in children - Stiegler, Petra; Sausenthaler, Stefanie; Buyken, Anette; Rzehak, Peter; Czech, Daniel; Linseisen, Jakob; Kroke, Anja; Gedrich, Kurt; Robertson, Claire; Heinrich, Joachim (Public Health Nutrition)
Abstract Objective The present paper describes the systematic development of an FFQ to assess the intake of fatty acids and antioxidants in school-aged children. In addition, a validation study applying 24 h dietary recalls was performed. Design Using the variance-based Max_r method, a list of eighty-two foods was compiled from data obtained by 3 d weighed dietary records. The foods were used to design an FFQ, the comprehensibility of which was evaluated in a feasibility study. In addition, the FFQ was validated in a subset of 101 children from the German Infant Nutritional Intervention Study (GINI PLUS) against one 24 h dietary recall. Results The feasibility study attested a good acceptance of the FFQ. Mean intake of foods compared well between the FFQ and the 24 h dietary recall, although intake data generated from the FFQ tended to be higher. This difference became less apparent at the nutrient level, although the estimated average consumption of arachidonic acid and EPA using the FFQ still exceeded values recorded with the 24 h recall method by 45 % and 29 %, respectively. Conclusions On the basis of the systematic selection process of the food list, the established practicability of the FFQ and the overall plausibility of the results, the use of this FFQ is justified in future epidemiological studies.

Glucocorticoids and body fat associated with renal uric acid and oxalate, but not calcium excretion, in healthy children - Shi, Lijie; Berkemeyer, Shoma; Buyken, Anette; Maser-Gluth, Christiane; Remer, Thomas (Metabolism)

Glycemic index in overweight development: distinguishing limited evidence from limits in evidence - Buyken, Anette; Günther, Anke LB; Barclay, Alan; Brand-Miller, Jennie; Schulze, Matthias B (The American Journal of Clinical Nutrition)

IT Productivity and Aggregation using Income Accounting - Kundisch, Dennis; Mittal, N.; Nault, B. (10th Workshop on Information Systems and Economics (WISE))

Enhancing the Quality of Financial Advice with Web 2.0 - An Approach considering Social Capital in the private Asset Allocation - Kundisch, Dennis; Zorzi, R. (Proceedings of the 15th Amercas Conference on Information Systems (AMCIS))

An Evaluation Framework for Tracker Certificates during the Financial Crisis and beyond - Kundisch, Dennis; Klein, C. (International Federation of Classification Societies 2009 Conference)

Technical Analysis as a Method of Risk Management - Dorfleitner, G.; Klein, C.; Kundisch, Dennis (Monetary Growth: Trends, Impacts and Policies)

Rezension zu L.J. Issing & P. Klimsa (Hrsg.) (2009). Online-Lernen. Handbuch für Wissenschaft und Praxis. München: Oldenbourg Verlag - Eickelmann, Birgit (Journal for Educational Research Online)

Proceedings of the 4th International Workshop on Enterprise Applications and Services in the Finance Industry

Selbstoptimierende Systeme des Maschinenbaus - Definitionen, Anwendungen, Konzepte - Adelt, P.; Donoth, J.; Gausemeier, Jürgen; Henkeler, S.; Kahl, S.; Klöpper, B.; Krupp, A.; Münch, E.; Oberthür, S.; Paiz, C.; Porrmann, M.; Radkowski, R.; et al.

Verlässlichkeit selbstoptimierender Systeme - Potenziale nutzen und Risiken vermeiden - Dell'Aere, A.; Hirsch, M.; Klöpper, B.; Koester, M.; Krüger, M.; Krupp, A.; Müller, T.; Oberthür, S.; Pook, S.; Priesterjahn, C.; Romaus, C.; Schmidt, A.; et al.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Proceedings of the 9th Dutch-Belgian Information Retrieval Workshop)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.
Keywords: company search; information extraction; sublanguage

Key Expression driven Record Mining for Event Calendar Search - Lee, Yeong Su; Geierhos, Michaela (KDML’09 Tagungsband. Workshop-Woche: Lernen - Wissen - Adaptivität. LWA 2009. 21.-23.09.2009)
This paper presents an approach to extract data records from websites, particularly ones with event calendars. We therefore use language-specific key expressions and HTML patterns to recognize every single event given on the investigated web page. One of the most remarkable advantages of our method is that it does not require any additional classification steps based on machine learning algorithms or keyword extraction methods; it is a so-called one-step mining technique. Our experimental results obtained on German opera websites show excellent results in precision and recall. Furthermore, we could demonstrate that our proposed technique outperforms other data record mining applications run on event sites.

Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Computational Linguistics and Intelligent Text Processing: 5th International Conference, CICLing 2004, Seoul, Korea, February 15-21, 2004, Proceedings)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.

Musterbasiertes Re-Engineering von Softwaresystemen - Meyer, Matthias

Dienste-Infrastrukturen für eLearning – Konzeption, Aufbau und Betrieb - Brennecke, Andreas; Finke, Stefan; Oevel, Gudrun; Roth, A. (Hochschulentwicklung innovativ gestalten – Das Projekt Locomotion an der Universität Paderborn)